Anatomy & physiology the unity of form and function - Saladin, Kenneth S.; Gan, Christian A. (New York, NY McGraw Hill LLC, 2024)
Anatomy & Physiology: The Unity of Form and Function tells a story comprised of many layers, including core science, clinical applications, the history of medicine, and the evolution of the human body. Saladin combines this humanistic perspective on anatomy and physiology with vibrant photos and art to convey the beauty and excitement of the subject to beginning students. To help students manage the tremendous amount of information in this introductory course, the narrative is broken into short segments, each framed by expected learning outcomes and self-testing review questions. This presentation strategy works as a whole to create a more efficient and effective way for students to learn A&P. Writing Style and Level Saladin's text is written using plain language for A&P students who may be taking this course early in their curricula. Careful attention has been given to word selection and paragraph structure to maintain the appropriate writing level for all students"-- Provided by publisher.
Includes index.
Keywords: Human anatomy -- Textbooks; Human physiology -- Textbooks